Sociological Explanation of Factors Affecting the Prevalence of Child Marriage (Case Study: Dishmok City) - Nasrollah Nosratikhah; Seyed Samad Beheshty; Maryam Mokhtari (جامعه شناسی کاربردی)
Introduction Marriage is often pursued to enhance one's quality of life and is a common practice among humans. A troubling manifestation of this is child marriage, which refers to formal or informal unions involving individuals, who have not yet reached the legal marriage age. This practice not only leads to severe physical and psychological harm for those involved, but also acts as a catalyst for various social issues. Given the significant influence of culture and societal norms on the prevalence of child marriage, this study aimed to investigate the social factors contributing to this phenomenon in Dishmok, a city in Kohgiluyeh and Boyer Ahmad Province.